2000
DOI: 10.1038/sj.ejcn.1600924
|View full text |Cite
|
Sign up to set email alerts
|

Appetite dysfunction in obese males: evidence for role of hyperinsulinaemia in passive overconsumption with a high fat diet

Abstract: Objective: To test the hypothesis that caloric and fat intake in a pre-load meal have no subsequent effects upon blood glucose and insulin concentrations, perceived hunger, subsequent food intake and appetite control in lean and obese men. Design: Lean and obese men reported to the laboratory in the morning in a fasted state where they were subject to an eating test based on the pre-load ± test meal paradigm, using a double-blind protocol. The breakfast preload was either a reduced caloric low-fat (LF) meal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
56
0
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 55 publications
(60 reference statements)
7
56
0
2
Order By: Relevance
“…16 Recently, Speechly and Buffenstein described an inverse relationship between insulin concentration 5.5 h after a ®xed meal and the subsequent food intake in lean subjects, but not in obese subjects. 19 The notion that insulin promotes satiety is supported by previous studies. 20 GIP and GLP-1 are known to be important incretin-hormones, 21 and in theory the increase in satiety produced by the intestinal handling of nutrients might, in part, be mediated through an increased insulin response.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…16 Recently, Speechly and Buffenstein described an inverse relationship between insulin concentration 5.5 h after a ®xed meal and the subsequent food intake in lean subjects, but not in obese subjects. 19 The notion that insulin promotes satiety is supported by previous studies. 20 GIP and GLP-1 are known to be important incretin-hormones, 21 and in theory the increase in satiety produced by the intestinal handling of nutrients might, in part, be mediated through an increased insulin response.…”
Section: Introductionsupporting
confidence: 74%
“…20 Speechly and Buffenstein have recently reported in lean subjects that insulin concentration before an ad libitum lunch, was inversely correlated to the energy intake. 19 In the present study an inverse correlation was found between responses of insulin and GLP-1 in obese subjects. It is well known that GLP-1 stimulates insulin release and we therefore suggest that this ®nding may re¯ect two independent effects of the obese state: reduction of meal induced GLP-1 release and increased insulin release.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…There was therefore no difference between diets on body weight or body fat. However, it would be of interest in further studies to determine the effects of AX fibre on acute postingestive satiety (Speechly & Buffenstein, 2000) as well as the long-term effects on body composition of diets supplemented with AX fibre and consumed ad libitum.…”
Section: Discussionmentioning
confidence: 99%
“…In lean individuals who are challenged with chronic overfeeding, resistance to obesity was directly predicted by spontaneous increases in activity (25). Conversely, BL6 mice, which consumed significantly more kilocalories per day when offered an energy-dense diet, may provide a more appropriate model for obese individuals with similar maladaptive responses, which are amplified by prolonged exposure to the typical modern environment of excess calories and reduced need for movement (10,37). Similarly to the BL6 strain, exposure of many humans to this environment translates to increased energy intake and decreased planned and spontaneous activity, ultimately leading to obesity in individuals without any inherent self-regulation to keep the process in check.…”
Section: Discussionmentioning
confidence: 99%